First-Time Mothers’ Relationship with their Child during the First Year: A Qualitative Narrative Analysis - Skirgailaitė, Barbora; Kaluževičiūtė, Greta (Psichologija, 2025)
The mother-child relationship is fundamental to both the child’s development and the mother’s psychological well-being. How mothers experience this bond is shaped by a range of personal, social, and cultural factors. This study explores how first-time mothers experience their relationship with their child one year after birth, focusing on the narratives that shape their perceptions of motherhood. Eight women aged 27 to 39 participated in the study; at the time of data collection, their firstborn children were between 12 and 18 months old. A qualitative approach was employed, using semi-structured interviews and narrative analysis. In this study, narrative is understood as a personal account of experience, shaped by individual meaning-making and broader socio-cultural influences. Analysis revealed five central themes reflecting different aspects of maternal identity and the narrative sources shaping motherhood: (1) the development of the relationship from a specific point in time, (2) the personality and character of the child, (3) the changes after becoming a mother, (4) the importance of the support of those around you at the beginning of motherhood, and (5) being a good mother – accepting and loving the child unconditionally. The participants described motherhood as a transformative experience that reshaped their sense of identity, often involving joy, a sense of self-loss, and fusion with the child. The process of ‘becoming a mother’ was interpreted in various ways – from pregnancy to the moment the child first addressed them as a ‘mom’. The study also reflects diverse motherhood narratives: motherhood as fulfilment, as instinct, and as shaped by cultural ideals of the ‘good mother’. This study contributes to psychological literature by illuminating the interplay between personal maternal experiences and the broader social and cultural narratives that influence how motherhood is understood and lived.